Implementation of Screening, Counseling, and Health Education for Hypertension Prevention among Adolescents - Marpatmawati, Idhfi; Sambas, Etty Komariah; Suprapti, Betty; Rismawan, Wawan; Wayunah, Wayunah; Yuningsih, Aneng; A, Saefunnuril; Hidayat, Nandita Milda; Setyarini, Wahyu Ikka; A, Iman Syarifuddin; Asparina, Arina; Bilhamdillah, Zalfa Nabilah; Gustiani, Mia Ruhmiati; Nuraeni, Nuraeni; Ramadhan, Gilang; Ismawi, Ade Sayid (Yayasan Inspirasi El Burhani, 2025)
Introduction: Hypertension is no longer a health issue limited to adults but increasingly affects adolescents. Its asymptomatic nature makes it difficult to detect early, while lifestyle factors such as poor diet, lack of physical activity, and stress significantly increase the risk. Early intervention through school-based programs is crucial to increase awareness and prevention. Objective: The purpose of this service was to provide promotive and preventive efforts against hypertension in adolescents at SMK Suryalaya, Tasikmalaya, by increasing their knowledge, awareness, and healthy lifestyle practices through health screening, education, and counseling Method: This public service was conducted by lecturers and students of Universitas Bakti Tunas Husada in collaboration with SMK Suryalaya. The program consisted of three stages: preparation, implementation, and evaluation. Screening included measurement of blood pressure, pulse, body mass index (BMI), and fitness tests. Health education was delivered through interactive lectures and discussions, while personal counseling was provided for students identified with health risks. Result: The activity involved 58 students (34 from grade X and 24 from grade XI). Screening results revealed 9.1% hypertension, 34.8% hypotension, and 13.6% obesity, indicating significant cardiovascular risks. Health education improved students’ knowledge with an average score increase from 60 (pre-test) to 82 (post-test), a gain of 36.7%, shifting most students from “moderate” to “high” knowledge categories. Personalized counseling for at-risk students enhanced their understanding and commitment to adopting healthier habits. Conclusion: This program demonstrated that integrating screening, education, and counseling effectively improved adolescent health awareness and promoted preventive behaviors. Early detection and health promotion in schools are essential strategies to reduce long-term cardiovascular risks. The program can serve as a replicable model for adolescent health promotion in other educational institutions.